2004
DOI: 10.5820/aian.1102.2004.109
|View full text |Cite
|
Sign up to set email alerts
|

Process Evaluation: How It Works

Abstract: Despite increasing prevalence of asthma among American Indians and/or Alaska Natives, little is known about their use of traditional healing in its management. A convenience sample of 24 Navajo families with asthmatic members (n=35) was interviewed between June 1997 and September 1998. While 46% of families had previously used traditional healing, only 29% sought traditional healing for asthma. Use of traditional healing was unrelated to use of biomedical therapies, hospitalizations, or emergency services. Pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Process evaluation. Process evaluations offer insight into how programs are being implemented and how participants experience them (Bess et al, 2004;Fink, 2015). By conducting process evaluations, evaluators can gain insight into strengths and weaknesses of programs and recommend adjustments (Fink, 2015).…”
Section: Types Of Program Evaluationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Process evaluation. Process evaluations offer insight into how programs are being implemented and how participants experience them (Bess et al, 2004;Fink, 2015). By conducting process evaluations, evaluators can gain insight into strengths and weaknesses of programs and recommend adjustments (Fink, 2015).…”
Section: Types Of Program Evaluationsmentioning
confidence: 99%
“…Evaluators should choose methodology and data collection methods that work best within the program and the larger context. Bess et al (2004) indicated the usefulness of qualitative methodologies when conducting process evaluations, recommending participant observation, content analysis, situational analysis, open-ended surveys, and interviews to capture a holistic picture of stakeholders' experiences. Process evaluations can lead to meaningful interpretation of outcome data as it provides insight into what was working and what needed to be adjusted in the process of implementing a program (Fink, 2015).…”
Section: Types Of Program Evaluationsmentioning
confidence: 99%
“…For this purpose, qualitative methods are most often used, which are defined in the context of evaluation as research methods that emphasize depth of understanding, that attempt to tap the deeper meaning of human experience, and that intend to generate theoretically richer, observations which are not easily reduced to numbers [32]. The most used qualitative evaluation methods include [33]: content analysis, situational analysis, in-house surveys and interviewing.…”
Section: Validation Verification and Evaluationmentioning
confidence: 99%
“…A small number of process evaluations have been conducted on reentry programs in the United States using qualitative data to report on the lived experience of those navigating the reentry process upon release and/or understandings of program success among attendees [84,85]. Often process evaluations proceed with qualitative methods to assess client experiences with the intervention [86] and may provide additional qualitative details (e.g., details on staffing and program delivery) to help build contextual insights [87].…”
Section: Introductionmentioning
confidence: 99%